Secondary Metabolites from a Culture of the Fungus Neosartorya pseudofischeri and Their In Vitro Cytostatic Activity in Human Cancer Cells - Eamvijarn, Amnat; Kijjoa, Anake; Bruyère, Céline; Mathieu, Véronique; Manoch, Leka; Lefranc, Florence; Silva, Artur; Kiss, Robert; Herz, Werner (Planta Medica, 2012)
Four known (1, 2, 3, and 6) and three new compounds including a 1,4-diacetyl-2,5-dibenzylpiperazine derivative (4), a quinazolinone-containing indole derivative (5), and a new ester of 2,4-dihydroxy-6-methylbenzoic acid (7) were isolated from the fungus Neosartorya pseudofischeri S. W. Peterson. Compound 2 displayed in vitro growth inhibitory activity that ranged between the activities of etoposide and carboplatin, chosen as reference compounds, in six distinct cancer cell lines. Compound 1 displayed less activity than 2. Computer-assisted phase-contrast microscopy-related analysis revealed that 2 displayed cytostatic, not cytotoxic, effects in human U373 glioblastoma and A549 non-small cell lung cancer apoptosis-resistant cells with marked inhibition of mitotic rates. Cancer cells in the remaining phases of the cell cycle were unchanged. Flow cytometry analysis further confirmed that 2 does not induce apoptotic features in U373 or A549 cancer cells. Thus, 2 represents a novel chemical scaffold from which derivatives for anticancer cytostatic compounds can be derived.
Keywords: Neosartorya pseudofischeri S. W. Peterson; Trichocomaceae; brasiliamide derivatives; pseudofischerine; pyripyropene A; cytostatic activity